HUMAN FACE IN EDUCATION: A PHILOSOPHICAL ANALYSIS AND CRITIQUE - Joseph Munyoki Mwinzi (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
A human face is one vital part that can be used to consciously or unconsciously express human emotions. The shape of the nose and the muscles of the face are significant when engaging in body language as a means of communication. The face therefore is not merely a set of frontage features, but it is more meaningful in its configuration, implying the reality of matter and form in our overall understanding of humanity. This is consistent with the view that an image is seen in its entirety, not by its individual parts. Thus, the human face of an individual is the cause of existential diversity in terms of variability whose inference is to enable recognition and identification of the uniqueness of individuality in order to discover the reality of being. In a similar vein, the human face analogy can elucidate meaning for education. In the academic spectrum, the subjects codified as humanities provide the analogy of face in education more so during   the   process   of   acquiring   knowledge.   As   such,   humanities   contribute   towards understanding perspectives, conceptualizing ideas, defining antiquities, isolating cultures and configuring creativity and by extension, fostering equity. In the contemporary society, science and technology is being overemphasized because it has contributed to human discoveries, inventions  and  innovations.  However,  it  is  palpable  that  science  and  technology  can  only interpret an idea using the component of a humanistic skill – dispositional knowledge which is devoid of propositional knowledge. It has no relevance in ideas, attitude, and values, which remain at the reserves of humanities. This article targets to shed more light on this discourse in order to inject newer insights in the unending controversy in science/humanities divide in education.